XacFhaB adhesin, an important Xanthomonas citri ssp. citri virulence factor, is recognized as a pathogen‐associated molecular pattern. (9th June 2016) - Garavaglia, Betiana S.; Zimaro, Tamara; Abriata, Luciano A.; Ottado, Jorgelina; Gottig, Natalia
Summary: Adhesion to host tissue is one of the key steps of the bacterial pathogenic process. Xanthomonas citri ssp. citri possesses a non‐fimbrial adhesin protein, XacFhaB, required for bacterial attachment, which we have previously demonstrated to be an important virulence factor for the development of citrus canker. XacFhaB is a 4753‐residue‐long protein with a predicted β‐helical fold structure, involved in bacterial aggregation, biofilm formation and adhesion to the host. In this work, to further characterize this protein and considering its large size, XacFhaB was dissected into three regions based on bioinformatic and structural analyses for functional studies. First, the capacity of these protein regions to aggregate bacterial cells was analysed. Two of these regions were able to form bacterial aggregates, with the most amino‐terminal region being dispensable for this activity. Moreover, XacFhaB shows features resembling pathogen‐associated molecular patterns (PAMPs), which are recognized by plants. As PAMPs activate plant basal immune responses, the role of the three XacFhaB regions as elicitors of these responses was investigated. All adhesin regions were able to induce basal immune responses in host and non‐host plants, with a stronger activation by the carboxyl‐terminal region. Furthermore, pre‐infiltration of citrus leaves with XacFhaB regions impaired X. citri ssp. citri growth, confirming the induction of defence responses and restraint of citrus canker. This work reveals that adhesins from plant pathogens trigger plant defence responses, opening up new pathways for the development of protective strategies for disease control.